Association between Perioperative Blood Transfusions and Clinical Outcomes in Patients Undergoing Bladder Cancer Surgery: A Systematic Review and Meta-Analysis Study. (31st January 2016) - Cata, Juan P.; Lasala, Javier; Pratt, Greg; Feng, Lei; Shah, Jay B.
Abstract : Background . Perioperative blood transfusions are associated with poor survival in patients with solid tumors including bladder cancer. Objective . To investigate the impact of perioperative blood transfusions on oncological outcomes after radical cystectomy. Design . Systematic review and meta-analysis. Setting and Participants . Adult patients who underwent radical cystectomy for bladder cancer. Intervention . Packed red blood cells transfusion during or after radical cystectomy for bladder cancer. Outcome Measurements and Statistical Analysis . Recurrence-free survival (RFS), cancer-specific survival (CSS), and overall survival (OS). We calculated the pooled hazard ratio (HR) estimates and 95% confidence intervals by random and fixed effects models. Results and Limitation . Eight, seven, and five studies were included in the OS, CSS, and RFS analysis, respectively. Blood transfusions were associated with 27%, 29%, and 12% reduction in OS, CSS, and RFS, respectively. A sensitivity analysis supported the association. This study has several limitations; however the main problem is that it included only retrospective studies. Conclusions . Perioperative BT may be associated with reduced RFS, CSS, and OS in patients undergoing RC for BC. A randomized controlled study is needed to determine the causality between the administration of blood transfusions and bladder cancer recurrence.